Development and Dissolution Study of a β-Galactosidase Containing Drinking Straw - Márton Király; Konrád Sántha; Barnabás Kállai-Szabó; Kriszta Mariann Pencz; Krisztina Ludányi; Nikolett Kállai-Szabó; István Antal (MDPI AG, 2022)
Today, in addition to many different physicochemical and pharmacological properties of the active ingredients and excipients, the developer of a pharmaceutical formulation must take into account several factors during the formulation process in order for the patient to cooperate to use the formulation accurately. One of the innovative solutions in paediatrics may be the use of medicated drinking straws. For our studies, we successfully prepared lactase-containing, rapid disintegration particles by two techniques commonly used in the pharmaceutical industry. The simulation of the usage of the filled straws was presented from a new perspective for the patient by an in vitro method. The effect of the temperature of the liquid used during the administration of the straw and the effect of the frequency during the application on the dissolution rate were investigated. According to our results, in the case of a straw containing rapidly dissolving particles, the temperature of the used liquid and the mode of administration (frequency) play a significant role in the release rate from the composition.